A faunal survey of nycteribiid flies (Diptera: Nycteribiidae) associated with bats in Paraguay - Graciolli, Gustavo; Dick, Carl W.; Gettinger, Donald (Zootaxa, 2006)
An extensive survey of ectoparasitic nycteribiid flies infesting bats in Paraguay provides information about their taxonomy and hosts at a geographic interface between subtropical and temperate habitats. During the study, 2,931 bats representing five families, 22 genera, and 45 species were captured and sampled for ectoparasites. Of these, 86 individuals belonging to six species of vespertilionid bats, and one individual of a molossid bat, harbored 150 fly specimens. We identified five species of Basilia Miranda-Ribeiro, with one, Basilia juquiensis Guimarães, representing a new record for Paraguay. In total, six species of Basilia have been reported to occur in Paraguay.